GAYA KOMUNIKASI DALAM KOMUNIKASI PASANGAN ETNIS CAMPUR DI PONDOK CINA-DEPOK JAWA BARAT - Santa Lorita Simamora (Jurnal Komunikasi, 2017)
Ethnography of Communication couples ethnic mix in Pondok China, Depok is the theme of research that aims to know the communication behavior of married couples ethnic mix in certain contexts, namely local ethnic and immigrant which each carry a different culture. Individuals married couples ethnic mix has the interpersonal relationships that are typical in a domestic life couples ethnic mix, has a lot of contexts, among others, dialects and attitude adjustment when communicating. Besides cultural pattern appears in every language, communication style in communication activities and communication behavior in accordance with the adopted individual cultural patterns. Every culture has its own communication style. Culture and communication are inseparable This difference is often one of the issues when related to household communications couples ethnic mix. So in this study researchers used ethnographic methods to examine the communication in the communication style of communication activities ethnically mixed couples in Pondok Cina in various contexts. The study was conducted with participant observation throughout the period of twenty-four months to ten couples ethnic immigrants from Aceh (Bireuen Lokhsemawe), Batak Mandailing, Central Java, Sunda, and Padang who has a husband / wife natives Kampung Bojong alias Pondok Cina, Depok, West Java. One study found that the results of studies showing that the communication ethnically mixed couples where they settle and live in a village area that is Pondok Cina partner, Depok. Ethnic immigrants represent adjustments communication styles in local ethnic couples. But seen also that dialect as a partner of cultural identity ethnic immigrants did not disappear entirely.  Keywords: Communication ethnically mixed couples, communication style ,, ethnography of communication.